Effect of job satisfaction on turnover intention: an empirical investigation on Nigerian banking industry - Ibrahim, Muhammad Garba; Abdullah, Haim Hilman; Kaliappen, Narentheren (Institut Pengurusan Kualiti (IPQ), 2016)
Extant literature revealed that job satisfaction has negative effect on employee turnover intention. Despite loss of job satisfaction and high turnover intention among many bank employees in Nigeria very little attention was devoted to examining the negative effect of job satisfaction on turnover intention in the industry. Drawing from 192 employees from 5 banks this study analyzes the effect of job satisfaction on turnover intention In Nigerian banking industry. Results of regression analysis revealed that there is significant negative relationship between job satisfaction and employee turnover intention in the Nigerian banking industry. Findings and implications were also discussed.